Frontline rituximab monotherapy induction versus a watch and wait approach for asymptomatic advanced‐stage follicular lymphoma: A cost‐effectiveness analysis. Issue 15 (15th April 2015) - Prica, Anca; Chan, Kelvin; Cheung, Matthew
<x xml:space="preserve">Abstract</x> BACKGROUND A watch and wait (WW) strategy is the standard of care for patients with asymptomatic advanced‐stage follicular lymphoma. Recent data have demonstrated an improvement in the time to progression with rituximab induction (RI) with or without rituximab maintenance (RM) in comparison with a WW strategy wait in such patients. It remains unclear whether this is a cost‐effective strategy. METHODS A Markov decision analysis model was developed to compare the clinical outcomes, costs, and cost‐effectiveness of RI (4 weekly doses) plus RM (12 doses every 2 months), RI (4 weekly doses), and a WW strategy for patients newly diagnosed with low‐burden, asymptomatic advanced‐stage follicular lymphoma over a lifetime horizon. Baseline probabilities and utilities were derived from a systematic review of published studies, and they were evaluated on a 6‐month cycle. A Canadian public health payer's perspective was adopted, and costs were presented in 2012 Canadian dollars. RESULTS RI was the cheapest strategy. It was less costly at $59, 953 versus $67, 489 for the RM arm and $75, 895 for the WW arm. It was also associated with a slightly lower quality‐adjusted life expectancy at 6.16 quality‐adjusted life years (QALYs) versus 6.28 QALYs for the RM strategy but was superior to WW (5.71 QALYs). In sensitivity analyses of key variables, this effectiveness was sensitive to the probability of first and second progression in the RI arm, and this indicated relatively neutral effectiveness between the 2 rituximab arms. CONCLUSIONS RI without maintenance for asymptomatic advanced‐stage follicular lymphoma is the preferred strategy: it minimizes costs per patient over a lifetime horizon. Cancer 2015;121:2637–2645. © 2015 American Cancer Society.